2005
DOI: 10.1098/rspa.2005.1488
|View full text |Cite
|
Sign up to set email alerts
|

Continuum damage mechanics predictions of creep damage initiation and growth in ferritic steel weldments in a medium bore branched pipe under constant pressure at 590 °C using a five-material weld model

Abstract: The paper reports three-dimensional creep continuum damage mechanics (CDM) analyses of creep failure in a medium bore Cr–Mo–V low alloy ferritic steel welded branched-pressure vessel that has been tested under a constant pressure of 4 MPa, at a uniform temperature of 590 °C. The use of the CDM computer software Damage XXX to analyse the initiation and growth of creep damage and subsequent failure in the branch weld is reported for a five-material model that includes: parent, Type IV, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…However, our current model cannot capture the decrease of the creep strain rate during the primary creep stage. To model the primary creep stage, more internal variables are required to describe the strain hardening effect [22,23]. This problem will be solved in our future work.…”
Section: Prediction Of the Local Response Of P92 Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our current model cannot capture the decrease of the creep strain rate during the primary creep stage. To model the primary creep stage, more internal variables are required to describe the strain hardening effect [22,23]. This problem will be solved in our future work.…”
Section: Prediction Of the Local Response Of P92 Steelmentioning
confidence: 99%
“…Klenk and his coworkers [20,21] proposed a modified Graham-Walles creep model to investigate type-IV cracking in high-Cr steel weldments. Hayhurst and his coworkers [22,23] proposed a continuum damage mechanism based model with three internal variables, which represent the strain hardening during primary creep, the volume of carbide precipitates and the intergranular cavitation damage, respectively. In Hyde's group [24,10], the type-IV cracking in P91 and P92 weldments are studied by using both a Kachanov-type creep law and a Liu-Murakamitype creep law.…”
mentioning
confidence: 99%
“…This is caused by the low effective stress and high first stress invariant in these regions, which in turn are a result of stress redistribution caused by the mismatch in the creep properties of the weld, HAZ, Type IV, and parent materials. The deficiency of the axisymmetric approach has been pointed out by Mustata et al [14] and Hayhurst et al [15], who concluded that it was necessary to carry out a full three-dimensional calculation. The results of these three-dimensional CDM analyses have been shown to compare well with the results of vessel tests for lifetimes, damage fields, and leakage routes.…”
Section: Modelling Based On Continuum Damage Mechanicsmentioning
confidence: 99%
“…The essential difference is in the materials data used and the consideration of stress redistribution in regions of the weldment [i.e. the k factor in R5 and equation (15)]. …”
Section: R5 Assessment Procedures [9]mentioning
confidence: 99%
“…Attempts have been made to estimate stress and strain distributions developed across the weldment and its consequences for type IV creep cavitation [5,21,22] using finite element analysis (FEA). Hayhurst and coworkers have extensively used physically based continuum damage mechanics (CDM) coupled with FEA to predict the creep damage evolution and failure life of the butt-welded components [23][24][25][26][27][28][29][30]. Hall and Hayhurst [17] and Perrin and Hayhurst [31] had developed creep constitutive equations of weldments considering the physical processes of dislocation substructural evolution, carbide coarsening and creep cavity nucleation and growth under multiaxial state of stress.…”
Section: Introductionmentioning
confidence: 99%